2022
DOI: 10.3389/fpsyt.2022.1018659
|View full text |Cite
|
Sign up to set email alerts
|

Cyberchondria, but not preventive behavior, mediates the relationship between fear of COVID-19 and somatic burden: Evidence from Russia

Abstract: BackgroundThere is extensive available research on the relationship between fear of COVID-19 pandemic and physical symptoms. This study was the first to examine the cyberchondria and COVID-19 preventive behavior as mediators of this relationship.MethodsA cross-sectional study was conducted from October to December 2021, during the fourth wave of the COVID-19 pandemic in Russia. The participants were 2,011 Russian-speaking volunteers aged 18 years and older. They completed questionnaires on somatic burden, cybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…Research has shown that fear of COVID-19 is associated with various psychological problems, including generalized anxiety (Muyor-Rodríguez, Caravaca-Sánchez & Fernández-Prados 2021;Stankovic et al 2021), health anxiety (Akbari et al, 2021), depression (Çıkrıkçı, Çıkrıkçı & Griffiths 2022;Rodríguez-Hidalgo et al 2020), somatic symptoms (Zolotareva 2022), and post-traumatic stress (Coloma-Carmona & Carballo 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that fear of COVID-19 is associated with various psychological problems, including generalized anxiety (Muyor-Rodríguez, Caravaca-Sánchez & Fernández-Prados 2021;Stankovic et al 2021), health anxiety (Akbari et al, 2021), depression (Çıkrıkçı, Çıkrıkçı & Griffiths 2022;Rodríguez-Hidalgo et al 2020), somatic symptoms (Zolotareva 2022), and post-traumatic stress (Coloma-Carmona & Carballo 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This may engender feelings of anxiety (Heeren et al, 2020;Starcevic, Schimmenti & Billieux 2020) and preoccupation with one's own health (Akbari et al 2021). Also, the unpredictability of COVID-19 pandemic may lead to a persistent state of fear, with further consequences being higher levels of somatization and somatic symptoms (Zolotareva 2022), as well as post-traumatic stress symptoms (Coloma-Carmona & Carballo 2021).…”
Section: Introductionmentioning
confidence: 99%